Examining the customer equity framework from a consumer perspective - ACHARYA, Abhijith Geethakrishna (Institutional Knowledge at Singapore Management University, 2009)
The customer equity framework proposed by Rust, Zeithaml and Lemon provides the theoretical basis for this study. Previous research has focused on customer equity from a business perspective. The current study explores customer equity from a consumer's perspective, examining the relative impact of the drivers of value equity and brand equity across two brands on purchase intention. Based on the responses of 221 students, who are the primary target for the two brands studied, the results show that quality and price–prestige relationships serve as drivers of value equity, whereas brand awareness and brand attitudes drive perceptions of overall brand equity. Further findings support the influence of brand and value equity on consumers’ purchase intentions.